2014
DOI: 10.1093/eurheartj/ehu179
|View full text |Cite
|
Sign up to set email alerts
|

Targeting prolyl-isomerase Pin1 prevents mitochondrial oxidative stress and vascular dysfunction: insights in patients with diabetes

Abstract: Pin1 drives diabetic vascular disease by causing mitochondrial oxidative stress, eNOS dysregulation as well as NF-kB-induced inflammation. These findings provide molecular insights for novel mechanism-based therapeutic strategies in patients with diabetes.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
69
0
1

Year Published

2015
2015
2023
2023

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 86 publications
(75 citation statements)
references
References 39 publications
5
69
0
1
Order By: Relevance
“…Using Pin1 -/ -transgenic mice, the authors confirmed the involvement of this enzyme in the hyperglycemia-induced mitochondrial superoxide overproduction. Finally, an increased Pin1 expression and activity was also found in the blood of type II diabetic patients and correlates with HbA1c and fasting plasma glucose concentrations (67). Pin1 activity also correlates with the concentration of 8-iso-prostaglandin F2a, a marker of oxidative stress.…”
Section: Glucose Metabolism and Ros Generationmentioning
confidence: 82%
See 1 more Smart Citation
“…Using Pin1 -/ -transgenic mice, the authors confirmed the involvement of this enzyme in the hyperglycemia-induced mitochondrial superoxide overproduction. Finally, an increased Pin1 expression and activity was also found in the blood of type II diabetic patients and correlates with HbA1c and fasting plasma glucose concentrations (67). Pin1 activity also correlates with the concentration of 8-iso-prostaglandin F2a, a marker of oxidative stress.…”
Section: Glucose Metabolism and Ros Generationmentioning
confidence: 82%
“…Regarding the potential pathways involved in hyperglycemia-induced ROS generation, an elegant study recently described the increased expression and activity of the peptidyl-prolyl cis-trans isomerase (Pin1) and of the Ser-36 phosphorylation by the growth factor adapter protein (p66Shc), associated with an increased mitochondrial superoxide concentration in human aortic endothelial cells exposed to high glucose concentrations (67) (Fig. 4).…”
Section: Glucose Metabolism and Ros Generationmentioning
confidence: 99%
“…Initial studies indicated that Pin1 suppresses basal eNOS activity in a manner analogous to the tonic suppression of eNOS activity by its association with caveolin-1 [83], a mechanism that may be of particular relevance in endothelial cells exposed to high glucose concentrations. Certainly, pharmacological inhibition or genetic deletion of Pin1 in diabetic mice was shown to be protective against mitochondrial oxidative stress, endothelial dysfunction and vascular inflammation [84,85]. Others have reported that the association of eNOS with Pin1 enables the dephosphorylation of Ser116 and stimulates NO production and demonstrated that a pharmacological inhibitor of Pin1 increased aortic eNOS Ser116 phosphorylation, endothelial dysfunction and hypertension, findings that were reproduced using Pin1-deficient mice [86].…”
Section: Interactions Indirectly Affecting Enos Functionmentioning
confidence: 98%
“…Highly increased Pin1 levels induce the onset of obesity, the nonalcoholic fatty liver disease, diabetes mellitus and atherosclerosis (Nakatsu et al, 2011(Nakatsu et al, , 2012Lu et al, 2013;Paneni et al, 2015). Additionally, Pin1 has a biphasic effect on the insulin receptor substrate pathway (Saltiel and Kahn, 2001).…”
Section: Pin1 Is Involved In the Metabolic Syndromementioning
confidence: 99%